Hysteroscopy: endometrial vascular dystrophy: misnomer - Eiran, Ekta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Endometrial vascular dystrophy is a name given to the typical appearance of endometrium on hysteroscopy where in dilated, tortuous, black, worm like capillaries are seen on the endometrial surface. This is a case of a 17-year-old girl who presented with menorrhagia. Pelvic Scan showed endometrial polyp. On hysteroscopy the typical picture of endometrial vascular dystrophy was seen. Though it has been thought to be due to thrombosed capillaries, not much literature is available on this topic. More study is required to understand the cause behind this phenomenon.